Estrés emocional en la práctica pedagógica docente en enseñanza remota en instituciones educativas de nivel primaria de Caballococha, Ramón Castilla 2021 - Roque Jarama, Augusto (2024)
The study is relevant as it provides an empirical answer to the question: What is the level of emotional stress in the teaching pedagogical practice in remote teaching in primary level educational institutions of Caballococha, Ramón Castilla 2021? To this end, the general objective was to describe the level of emotional stress in their pedagogical practice in remote teaching, and to achieve this, the application of the descriptive, univariate, field and cross-sectional type was designed as a methodology. The study units were 192 teachers being at the same time the population and sample. To obtain relevant information, a questionnaire validated by experts was prepared and applied using the survey technique. The study concludes: That the level of emotional stress in the pedagogical practice of 192 (100.0%) teachers, 92.7% (178) present a medium stress level, 4.2% (8) high level and 3.1% (6) low level and the Kolmogorov-Smirnov normality test with the student’s t parametric test show results that indicate the hypothesis proposed for the research is demonstrated.